2016
DOI: 10.1002/2211-5463.12085
|View full text |Cite
|
Sign up to set email alerts
|

Expression of nephronectin is enhanced by 1α,25‐dihydroxyvitamin D3

Abstract: The extracellular matrix protein nephronectin (Npnt), also called POEM, is considered to play critical roles as an adhesion molecule in development and functions of various tissues, such as the kidneys, liver, and bone. In the present study, we examined the molecular mechanism of Npnt gene expression and found that vitamin D3 (1α,25‐dihydroxyvitamin D3,VD3) strongly enhanced Npnt mRNA expression in MC3T3‐E1 cells from a mouse osteoblastic cell line. The VD3‐induced increase in Npnt expression is both time‐ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…More recently, Wnt3a was reported to enhance Npnt mRNA expression in osteoblast‐like MC3T3‐E1 cells, thus increasing osteoblast differentiation via the Wnt/β‐catenin signaling pathway (Ikehata et al, ). The expression of NPNT mRNA is also enhanced in MC3T3‐E1 osteoblastic cells by the addition of 1α,25‐dihydroxyvitamin D 3 , a hormonally active metabolite of Vitamin D (Hiranuma et al, ).…”
Section: Npnt Function and Expression Regulation In Osteoblastsmentioning
confidence: 99%
“…More recently, Wnt3a was reported to enhance Npnt mRNA expression in osteoblast‐like MC3T3‐E1 cells, thus increasing osteoblast differentiation via the Wnt/β‐catenin signaling pathway (Ikehata et al, ). The expression of NPNT mRNA is also enhanced in MC3T3‐E1 osteoblastic cells by the addition of 1α,25‐dihydroxyvitamin D 3 , a hormonally active metabolite of Vitamin D (Hiranuma et al, ).…”
Section: Npnt Function and Expression Regulation In Osteoblastsmentioning
confidence: 99%
“…Npnt gene expression is seen in calcification tissues, especially in osteoblasts, thus in order to investigate osteoblast functions, we have performed experiments to elucidate the pattern of Npnt gene expression with several different reagents. In previous studies, we found that 1α,25-dihydroxyvitamin D 3 and Wnt3a promoted Npnt gene expression 8 , 9 , whereas TGF-β, TNF-α, IL-1β, OSM, FGF-2, and inorganic phosphate suppressed that expression 10 15 . Those results suggest that Npnt gene expression in osteoblasts is regulated via various factors.…”
Section: Introductionmentioning
confidence: 77%
“…(Table 4) Discussion Nephronectin is a highly conserved ECM protein that plays critical roles in regulating cell adhesion, differentiation, and survival. It acts as adhesion molecule and is involved in morphogenesis and functions of various tissues, such as the kidneys, liver, and bone [10,15].…”
Section: Resultsmentioning
confidence: 99%